Building revolutionary subjectivity: creative tensions in the Plataforma de Afectados por La Hipoteca. Issue 5 (3rd July 2020) - Berglund, Oscar
ABSTRACT: The paper assesses the Spanish housing activists Plataforma de Afectados por La Hipoteca (PAH, Platform for the Mortgage-Affected) as an example of left-wing convergence. From the perspective of the horizontal democratic practices and civil disobedience tactics they adopt, the paper acknowledges the anarchist, Marxist and reformist influences in PAH and reveals how the creative tension between activists of different persuasions has aided the movement's relative success. In harnessing and transforming the revolutionary subjectivity of the movement of the squares in 2011, PAH has in turn led to a broader urban radical politics. This new revolutionary subjectivity captures PAH's legacy and positioning within broader anti-austerity politics.